2020
DOI: 10.2478/hukin-2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

Differences in External Load Variables Between Playing Positions in Elite Basketball Match-Play

Abstract: The purpose of this study was to describe the specific demands and structure of interrelationships of external load variables in order to generate a position-related time motion profile in elite basketball. Seventeen professional players from three different playing positions (6 guards, 4 forwards, and 7 centers) were analyzed in five friendly games. Player load per minute (PLmin) was used as an indicator of intensity to compare positions. Furthermore, high and total external variables of jumping (hJUMP and tJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
0
21
1
Order By: Relevance
“…The present study showed no significant differences for integrated load or duration based on playing position. Previous research investigating external load in basketball by position has concluded that acceleration, deceleration, change of direction, and intensity demands varied based on position (i.e., centers, and forwards; Svilar et al, 2018;Salazar et al, 2020a). However, the absence of differences between positions in the present study suggests that positional categorizations may be less important when evaluating global measures of external load (e.g., player load) and developing training plans throughout an NBA season.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The present study showed no significant differences for integrated load or duration based on playing position. Previous research investigating external load in basketball by position has concluded that acceleration, deceleration, change of direction, and intensity demands varied based on position (i.e., centers, and forwards; Svilar et al, 2018;Salazar et al, 2020a). However, the absence of differences between positions in the present study suggests that positional categorizations may be less important when evaluating global measures of external load (e.g., player load) and developing training plans throughout an NBA season.…”
Section: Discussioncontrasting
confidence: 69%
“…Describing external load based on individual player characteristics is also important in better understanding the training dose-response relationship over time. Differences in basketball player characteristics that have been previously investigated include position (Svilar et al, 2018;Salazar et al, 2020a) and playing rotation status (Conte et al, 2018;Vazquez-Guerrero et al, 2018). Professional basketball can employ a wide range of experience levels, from draftees right out of college to veteran players who have been in the NBA for decades.…”
Section: Introductionmentioning
confidence: 99%
“…As in previous studies in basketball (Svilar et al, 2018;Salazar et al, 2020), a combination of variables was used to estimate the frequency of total and high-intensity actions. This strategy provided more detailed information on the physical demands of the players (Fox et al, 2020).…”
Section: External Load Variablesmentioning
confidence: 99%
“…These results showed differentiated variables of importance to match performance for defenders (i.e., distances at different intensities, sprint, PL, impacts, speed, acceleration, maximum decelerations, heart rate, and impacts), forwards (i.e., heart rate, accelerations and the distance at different intensities, decelerations, sprint, TL, maximum speed, and impacts), and midfielders (i.e., distances at different intensities, accelerations, speed, decelerations, heart rate, impacts, and sprints). In basketball, Salazar, et al (2020) analyzed 17 professional players from three different playing positions (guards, forwards, and centers) during friendly games and identified 3–4 different PC, related to playing positions. Specifically, game demands for guards involved total and high-intensity changes of direction and high-intensity decelerations and jumps, game demands for forwards were mainly total and high-intensity changes of direction, total accelerations, and high-intensity decelerations, and game demands for centers were total and high-intensity jumps, high-intensity decelerations, and total accelerations.…”
Section: Introductionmentioning
confidence: 99%